Glosa do uchwały NSA z dnia 23 maja 2016 r. (II FPS 6/15) - Mariański, Adam; Barwaniec, Aleksandra (Kwartalnik Prawa Podatkowego, 2016)
Commented resolution takes into consideration the legal nature of decision on liability of heirs regulated in Art. 100 of the General Tax Act. The gloss analyzes this regulation both in current and previous legal state (until the end of 2015). There are presented opposite standpoints referring to constitutive and declarative nature of mentioned decision, which are based on argumentation presented in tax law doctrine and administrative courts’ jurisdiction. Attention was paid on conclusions included in the justification of glossed resolution, its view has been approved by the Authors. As the summary, there are presented conclusions concerning practical importance of commented resolution.